BA’ZI 3d - METALLARNING 3-AMINO-1,2,4–TRIAZOL ASOSIDAGI KOMPLEKS BIRIKMALARINING TADQIQOTI - Chalaboyeva, Zilola; Razzoqova, Surayyo; Torambetov, Batirbay; Kadirova, Shahnoza (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
New complex compounds of Co (II), Ni (II) and Cu (II) nitrates were synthesized on the basis of 3-amino-1,2,4-triazole ligand, and the composition and structure of the synthesized complex compounds were determined using modern physicochemical methods studied. The results of IR-spectroscopic analysis of the structure of the obtained compounds showed that complexes with an octahedron structure are formed, where it was determined that the coordination took place through the second nitrogen atom in the triazole ring.